The criminalization of migration : context and consequences - Atak, Idil; Simeon, James C. (McGill-Queen's refugee and forced migration studies ;, 2018)
"This book examines "crimmigration"--The criminalization of migration -- from national and comparative perspectives, drawing attention to the increasing use of criminal law measures, public policies, and practices that stigmatize or diminish the rights of forced migrants and refugees within a dominant public discourse that not only stereotypes and criminalizes but marginalizes forced migrants. Leading researchers, legal scholars, and practitioners provide in-depth analyses of theoretical concerns, legal and public policy dimensions, historic migration crises, and the current dynamics and future prospects of crimmigration. The editors situate each chapter within the existing migration literature and outline a way forward for the decriminalization of migration through the vigorous promotion and advancement of human rights."--